2017
DOI: 10.1039/c7cc05986h
|View full text |Cite
|
Sign up to set email alerts
|

Acetylene hydrochlorination using Au/carbon: a journey towards single site catalysis

Abstract: The replacement of mercuric chloride in the production of vinyl chloride monomer, a precursor to PVC, would greatly reduce the environmental impact of this large scale industrial process. The validation of single Au cations supported on carbon as the best catalyst for this reaction at an industrial scale has resulted from nearly 35 years of research. In this feature article we review the development of this catalyst system and address the limitations of a range of characterisation techniques used previously wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 108 publications
1
67
0
Order By: Relevance
“…recently demonstrated using in situ X‐ray absorption spectroscopy (XAS) studies that the active form of the Au/C catalyst used for acetylene hydrochlorination is comprised of atomically dispersed AuCl x species, which are thermally stable under high‐temperature conditions (i.e., 200 °C) . The acetylene hydrochlorination reaction is proposed to occur through the Au I –Au III redox cycle as predicted through correlations with standard electrode potentials, which suggested to us that this catalyst could also be active as a homocoupling catalyst . In this study, we have investigated this Au/C single‐site catalyst for the homocoupling of phenylboronic acid and compared its performance to that of a sol‐immobilised Au/C nanoparticle catalyst and a simple gold salt (HAuCl 4 ).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…recently demonstrated using in situ X‐ray absorption spectroscopy (XAS) studies that the active form of the Au/C catalyst used for acetylene hydrochlorination is comprised of atomically dispersed AuCl x species, which are thermally stable under high‐temperature conditions (i.e., 200 °C) . The acetylene hydrochlorination reaction is proposed to occur through the Au I –Au III redox cycle as predicted through correlations with standard electrode potentials, which suggested to us that this catalyst could also be active as a homocoupling catalyst . In this study, we have investigated this Au/C single‐site catalyst for the homocoupling of phenylboronic acid and compared its performance to that of a sol‐immobilised Au/C nanoparticle catalyst and a simple gold salt (HAuCl 4 ).…”
Section: Resultsmentioning
confidence: 74%
“…XPS analysis of this 1 % Au/C (AR) sample also suggested the presence of metallic Au. However, it is now well recognised that Au–Cl x species supported on carbon can be susceptible to reduction by the X‐ray flux used in XPS analysis resulting in the generation of Au clusters and nanoparticles from highly dispersed cationic species …”
Section: Resultsmentioning
confidence: 99%
“…However, due to continuing efforts to protect the environment, the use of HgCl 2 has been increasingly limited, and its use for the synthesis of VCM has been prohibited since 2013; moreover, a comprehensive mercury-free ban is scheduled to be implemented in 2022. 1 It is thus urgent to search for an alternative mercury-free catalyst for the acetylene hydrochlorination reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In his initial study the activity of metal catalysts is found to be related with the associated metal ions' standard electrode potentials [1] and AuCl 3 has a higher electrode potential. Subsequently, there was a great deal of research on gold catalysts [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. However, Au-based catalysts do not have their advantages of economic performance because of the high price of Au.…”
Section: Introductionmentioning
confidence: 99%